Factores asociados a mortalidad, en pacientes hospitalizados por COVID-19 en UCI del Hospital Regional de Loreto de enero-junio 2021 - Laulate Rodriguez, Heiko Bleher (2022)
At the beginning of the year 2020, the COVID-19 disease had increased exponentially, becoming a pandemic. And in our region so far no studies have been conducted that demonstrate the factors associated with poor prognosis. The present investigation had as objectives the identification of the sociodemographic factors, the clinical characteristics, the laboratory findings and the type of treatment received, which are associated with mortality from COVID-19 in patients hospitalized in an intensive care unit from the month of January to June 2021. The study is observational, cross-sectional, descriptive. That included patients over 18 years of age with a confirmatory diagnosis of COVID-19 by PCR, antibody test or antigenic tests, registered as recovered or deceased at hospital discharge and those with incomplete or illegible data were excluded. 166 patients with a confirmed diagnosis of COVID-19 were included. The mean age was 58 years (SD: 13.8) and 108 (65.1%) were male. 59% belonged to the district of Iquitos and the most frequent comorbidity was arterial hypertension (65.6%), obesity in any degree (46.4%) and diabetes mellitus (29%). The most frequent symptoms were dyspnea (95.8%), fever (95.2%), cough (94.6%), sore throat and rhinorrhea (37.3%). A total of 115 cases died from COVID-19, which represented a fatality rate of 69.3%. Significant differences were found between the condition at discharge and age, sex, obesity, arterial hypertension, and if they presented clinical manifestations of cough on admission (p < 0.05). Those with various inflammatory markers such as elevated leukocytosis, CRP, procalcitonin, LDH, D-dimer, ferritin, and fibrinogen, were significantly associated with mortality. In addition, those with hypoxemia due to PaFiO2 less than 100mmHg were statistically significant (p < 0.001).